A CARE-compliant article: ipsilateral progressive idiopathic lipid keratopathy. Issue 35 (August 2019) - Pang, Yilin; Zhang, Qin; Bao, Yongzhen
Abstract: Rationale: Lipid deposition on the cornea without previous infection, inflammation, vascularization, or trauma is idiopathic lipid keratopathy. In vivo laser confocal microscopy (IVCM) and anterior segment optical coherence tomography (AS-OCT) are 2 noninvasive methods that can help identify the structures and morphological characteristics of the focus. Patient concerns: A 63-year-old woman with ipsilateral corneal lipid deposits developing from a small white spot into a yellow-white superotemporal elliptic shape within a year. AS-OCT showed peripheral deep stromal deposits. IVCM showed hyper-reflective material with typical crystalline-like or needle-like structures in the superotemporal area. Diagnosis: Idiopathic lipid degeneration. Interventions: Topical steroids eye drops 3 times a day for a month and further consultation every 3 months. Outcomes: This patient of idiopathic lipid keratopathy was observed every 3 months and till now we have reviewed this patient twice. Topical steroids eye drops were only used during the first month. No further development was observed about the lesion and the patient's visual acuity remained good. Conclusion: IVCM and AS-OCT can help identify the characteristic crystalline-like or needle-like hyper-reflective material that could help diagnosis of idiopathic lipid degeneration.